Playing under pressure: EEG monitoring of activation in professional tennis players - Pineda, S. (Physiology & Behavior, 2022)
The aim of this study was to monitor the activation during a neutral situation imagery (NSI) and a pressure situation imagery (PSI), based on the analysis of heart rate, brain waves and subjective ratings in athletes. The sample was made up of sixteen professional tennis players. Imagery protocols consisted of 3 phases; the first and the third involved being focused on their deep breathing (2 min.); the second, in the NSI, first service routine (17 s. - 1 min. 21 s.) and in the PSI, a match pressure situation (2 min. 10 s.). Results showed that both NSI and PSI increased heart rate. This increase was higher in the PSI and its highest point was at the maximum pressure moment: interval 5-6. In the case of brain waves, both NSI and PSI caused a decrease in gamma wave activity (intervals 3-8). In the PSI, there was also an increase in gamma waves in interval 5-6, the maximum pressure moment. Entropy was lower in the NSI. In regard to subjective ratings, in the psychological skills there were only significant differences in the PSI between pre- and post-activation at the during moment (pressure). In the imagery reality, olfactory and gustatory dimensions were the most difficult to perceive as real in the NSI and only the olfactory in the PSI.